Changes in infants' ability to switch visual attention in the first three months of life. - Atkinson, J; Hood, B; Wattam-Bell, J; Braddick, O (1992)
The abilities of 1-month-old and 3-month-old infants to shift their gaze from a central target to a peripheral target were compared in four experiments. In experiment 1 targets matched in mean luminance to the background were presented to infants in the periphery at varying levels of contrast. The contrast thresholds for target detection were found to be significantly different for 1-month-olds compared with 3-month-olds. With targets set close to these contrast thresholds, correct refixations and the latency for shifting attention were examined in experiment 2. Two conditions were used: a peripheral target was presented against a homogeneous background (noncompetition); and in the second condition, the patterned target appeared at one of two lighter peripheral windows set against a darker background (competition). Although there was no difference between the two age groups in the latency for shifting visual attention, 1-month-olds were found to make more directional errors in the competition condition. The competition effect of two potential targets on latencies was examined in experiment 3. In the competition condition, two identical peripheral patterned targets were presented to the infants. The 3-month-olds refixated more quickly to one of the double targets in the competition condition than to a single peripheral target, whereas 1-month-olds were slowed down by a double target display. Finally, in experiment 4 the ability of the infants to process and disengage from a central stimulus and to refixate towards a similar peripheral target was examined. This type of competition disrupted both the direction of the first eye movement and the latency to shift attention in both age groups. However, the effect was significantly greater for the 1-month-olds. Taken together, the results of these experiments demonstrate the greater disruption of fixation-shift behaviour in 1-month-olds compared with 3-month-olds when competing visual stimuli are used. This developmental change is explained in terms of maturation of executive cortical orienting systems over the first months of life.